The Effect of Sustainability Report Disclosure on Company Value 2017-2019 (The Effect of Sustainability Report Disclosure on Firm Value) - Astuti, Mety (Budapest International Research and Critics University, 2024)
This research aims to empirically test the disclosure of the Sustainability Report on firm value. The sample for this research was 22 companies that took part in ASRRAT (Asia Sustainability Report Rating) for the 2018-2020 period and were listed on the Indonesia Stock Exchange. The research method used is multiple linear regression analysis processed with SPSS 22. Based on the research results, it is concluded that the sustainability report has no effect on company value as proxied by Tobins Q, and there is no significant impact of disclosure of sustainability reports on companies that take part in ASRRAT consecutively. - contributes to firm value.